Drawing the line: a comment on CDP's classification of LDCs - Rieger, Hans Christoph (Internationales Asien-Forum, 1992)
The paper examines the efforts of the United Nations Committee on Development Planning to redefine the concept of "Least Developed Countries", as presented in the preceding paper by Udo E. Simonis. While the endeavour to provide a rule for determining the inclusion of a given country in the set eligible for aid on concessional terms is laudable, a number of questions are raised regarding the indicators proposed. In particular, the paper takes issue with Simonis’ statement that underdevelopment is being newly defined.
Elektronische Reproduktion der Druckausgabe
Keywords: Asien; Afrika; Ozeanien; Vierte Welt